Preparation method of high-strength SiC-based composite ceramic material
By hot-pressing sintering SiC powder, WC powder, aluminum source and carbon source, using the solid solution of WC and Al, the problems of low density and brittleness of SiC ceramic materials are solved, and high-strength and high-toughness SiC matrix composite is achieved Preparation of ceramic materials, suitable for industrial production.
Patent Information
- Application Number
- CN202310817569.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-05
AI Technical Summary
The existing SiC ceramic materials have limited their application due to the low density and brittleness of silicon carbide, and the high density of tungsten carbide limits its use range, making it difficult to effectively enhance the strength and toughness of SiC ceramics.
By mixing SiC powder, WC powder, aluminum source and carbon source, hot press sintering, using WC as the second phase reinforcement, combining the solid solution and deoxygenation of Al, a high-strength SiC-based composite ceramic material was prepared.
The high density, high strength and high fracture toughness of SiC ceramic materials are achieved, reducing density, while maintaining the excellent performance of low-density ceramics, simplifying the preparation process, and suitable for industrial production.
Smart Images

Figure CN119263846A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a high-strength SiC-based composite ceramic material, and belongs to the field of composite material preparation. Background Art
[0002] SiC ceramics have low density, high elastic modulus, high strength, low thermal expansion coefficient, and excellent wear resistance and corrosion resistance, so they are widely used in industrial fields such as petrochemicals, aerospace, energy and environmental protection, and mechanical electronics. However, since silicon carbide is a stable compound with strong covalent bonds and a low thermal diffusion coefficient, it is difficult to sinter and densify. At the same time, silicon carbide ceramics have defects such as high brittleness, easy cracking, and short service life, which limit their application. Therefore, it is urgent to develop a new type of high-density, high-strength silicon carbide ceramics.
[0003] Tungsten carbide (WC) has a hardness similar to that of diamond, good toughness, high chemical stability, and strong resistance to impact loads and friction and wear. However, the density of WC is 15.63g / cm 3 Much larger than SiC ceramic 3.20g / cm 3 , which limits its scope of use. The excellent mechanical properties of tungsten carbide can effectively increase the strength and toughness of silicon carbide ceramics. Chinese Patent Document 1 (Publication No. CN102173823A) discloses a silicon carbide / tungsten carbide composite material and a preparation method thereof, and a composite powder is prepared by wrapping SiC with WC, but it is limited to strengthening the metal matrix. Chinese Patent Document 2 (Publication No. CN101823882A) prepares a silicon carbide-tungsten carbide composite material with adjustable density that is very suitable for making an iron-based reinforcement phase. However, the reinforcing effect of tungsten carbide as the second phase of the material is not reflected. Chinese Patent Document 3 (Publication No. CN106242574A) discloses a tungsten carbide-based composite ceramic mold material and a preparation method thereof, which has excellent fracture toughness, flexural strength and friction reduction performance. However, the mass percentage of tungsten carbide in the preparation method is much greater than the mass percentage of silicon carbide, resulting in a higher density of the material. Chinese Patent Document 4 (Publication No. CN109809822A) adds tungsten carbide to prepare a high-strength and high-toughness silicon carbide ceramic carrier, but the density of the material is not high. Therefore, the preparation of high-strength SiC-based composite ceramic materials using the low density of silicon carbide and the excellent mechanical properties of tungsten carbide is a problem that needs to be solved by the present invention. Summary of the invention
[0004] To this end, the present invention provides a method for preparing a high-strength SiC-based composite ceramic material, comprising: (1) mixing SiC powder, WC powder, an aluminum source and a carbon source to obtain a mixed powder; (2) Hot pressing and sintering the mixed powder to obtain the high-strength SiC-based composite ceramic material.
[0005] In the present invention, WC is used as an excellent second phase reinforcement to prepare a high-strength silicon carbide composite ceramic material by hot pressing and sintering. Among them, Al enters the SiC lattice through solid solution to reduce the grain boundary energy. At the same time, Al also has a deoxidation effect. As the WC content increases, the solid solution effect weakens and the deoxidation effect increases.
[0006] Preferably, the SiC powder is α-SiC powder with a particle size of ≤1 μm; and the WC powder has a particle size of ≤2 μm.
[0007] Preferably, the total weight of SiC powder, WC powder, aluminum source and carbon source is 100wt%, wherein SiC powder accounts for 44% to 88% and WC powder accounts for 10% to 50%.
[0008] Preferably, the aluminum source is at least one of aluminum powder and aluminum oxide powder; the added amount of the aluminum source is 1 to 3 wt % of the total mass of the mixed powder.
[0009] Preferably, the carbon source is at least one of carbon black, activated carbon, graphite, glucose, starch and phenolic formaldehyde; and the amount of the aluminum source added is 1 to 3 wt % of the total mass of the mixed powder.
[0010] Preferably, the mixing method is ball milling; The SM-QB planetary ball mill is used for ball milling mixing, and its parameters include: the ball milling medium is anhydrous ethanol, the ratio of the ball milling medium to the mixed powder is (0.5-1):1; the ball-to-material ratio is (3-1):1, preferably 2:1; the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
[0011] Preferably, the grinding balls used for the ball milling and mixing are composed of large silicon carbide balls and small silicon carbide balls in a mass ratio of (0.1-10):1; wherein the diameter of the large silicon carbide balls is 10mm-30mm, and the diameter of the small silicon carbide balls is 1mm-5mm.
[0012] Preferably, after the ball milling is completed, the mixture is dried and sieved; the drying temperature is 60-70° C. and the time is 24-36 hours; and the sieving is through a 80-200 mesh sieve.
[0013] Preferably, the parameters of the hot pressing sintering include: a pressure of 30-40 MPa, a temperature of 2000-2150° C., and a time of 30-60 minutes.
[0014] Furthermore, preferably, the parameters of the hot pressing sintering include: First, the temperature is raised to 600-700°C at a heating rate of 15-25°C / min, and the pressure is adjusted to 10-20MPa; Then, the temperature is raised to 1000°C to 1100°C at a heating rate of 15 to 25°C / min; Adjust the heating rate to 8-12°C / min and continue to heat to 1500-1800°C, and adjust the pressure to 30-40MPa; The second heating rate is adjusted to 5-7°C / min and the temperature is continued to rise to 2000-2150°C and the temperature is kept at a constant temperature and pressure for 30-60 minutes; Finally, the furnace is cooled to room temperature and the pressure is released.
[0015] Beneficial effects: 1. The present invention adopts a carbothermal reduction method to remove silicon oxide on the surface of SiC powder to obtain a densified sintered silicon carbide ceramic; 2. The present invention utilizes the excellent mechanical properties of WC and the low density of SiC ceramics to enable the WC / SiC composite ceramic material to obtain relatively low density and high bending strength and fracture toughness and other mechanical properties; 3. The present invention provides a method for preparing a high-strength SiC-based composite ceramic material. The method is simple and easy to operate, has a short preparation cycle, strong practicability, low cost, and can be scaled up, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD pattern of SiC-WC composite ceramics. SiC and WC are the main phases in all samples, and there is also a small amount of carbon; Figure 2 The SEM image and corresponding EDS mapping of SiC-WC-40. In EDS, it can be observed that the aluminum element has aggregated. In addition, the distribution of O and Al elements is very matched; the SEM image shows that the O element is combined with Al at the grain boundary. This shows that the Al added to the sample has the effect of a deoxidizer; Figure 3 The XPS Al2p spectra of (a) SiC-WC-0 and (b) SiC-WC-40 show that the Al 2p spectra ( Figure 3 (a) can be fitted with two peaks located at 73.29 and 74.93 eV, which correspond to the Al-C bond of Al solid solution entering the SiC lattice and the Al-O bond of Al2O3 generated by Al deoxidation. Figure 3 In (b), a peak at 74.76 eV can be fitted, which is attributed to the Al-O bond. XPS results show that with the addition of WC, the solid solution (Al-C bond) disappears, and all Al elements react with oxides (SiO2, WO3) to form Al2O3 (Al-O); Figure 4 This is an SEM image of the crack propagation on the Ar+ etched surface of the SiC-WC composite. In the sample SiC-WC-50, the offset and bridging of WC particles and the stopping of the crack by WC particles can be seen. However, in the monolithic SiC, the crack extends rapidly and grain penetration fracture is observed. This shows that WC as a second phase particle can increase crack deflection and bridging, well inhibit crack propagation, and improve the fracture toughness of the composite ceramic; Figure 5 The Raman spectra of SiC and SiC-50wt%WC samples. It can be seen from the figure that WO bonds are generated on the worn surface of SiC-50wt%WC sample, indicating that the SiO2 film on the worn surface is transformed into WO3 film; Figure 6 The friction coefficient curve (a), average friction coefficient (b), cross-sectional depth profile (c) and specific wear rate (d) of SiC-WC composite ceramics with different WC contents. Figure 6 As can be seen from the contour line in (c), the wear rate of the SiC-WC-50 sample is significantly lower than that of the monolithic SiC ceramic. Figure 6 (d)) from 15.23×10 -7 mm 3 -N -1 -m -1 Down to 6.67×10 -7 mm 3 -N -1 -m -1 , down 56.2%; Figure 7 This is the XRD diagram of SiC-WC-10 with Al and B4C as sintering aids. It can be seen from the figure that the sample with B4C has the presence of W2B5 peak, indicating that the B element in WC and B4C reacts to form W2B5, thereby reducing the material performance; Figure 8 The Gibbs free energy diagram of the reaction between WC and B4C shows that the reaction can proceed spontaneously at a sintering temperature of 2150°C. DETAILED DESCRIPTION
[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0018] In the present disclosure, SiC and WC powders are mixed in proportion, and an aluminum source and a carbon source are added to perform planetary ball milling to obtain a uniformly mixed raw material powder. The uniformly mixed powder is sieved and then sintered to form the composite ceramic block. The present invention maintains the excellent performance of SiC ceramics with low density while significantly improving the bending resistance of the composite ceramic, so that the composite ceramic block has excellent mechanical properties.
[0019] The following is an exemplary description of a method for preparing a high-strength SiC-based composite ceramic material.
[0020] Add SiC powder (α-SiC powder), WC powder, aluminum source and carbon source into a ball mill and mix them evenly to obtain a mixed slurry. Among them, SiC accounts for 48% to 88%, and WC accounts for 10% to 50%. Preferably, the particle size of SiC powder is ≤1μm; preferably, the particle size of WC powder is ≤2μm. Preferably, the ball mill uses a SM-QB planetary ball mill. The preferred ball milling parameters are: the ball milling medium is anhydrous ethanol; the ball-to-material ratio is 2:1; the ball mill speed is 200 to 400r / min, and the ball milling time is 4 to 12h. Among them, the preferred grinding balls are composed of large silicon carbide balls and small silicon carbide balls with a mass ratio of 0.1 to 10:1, the diameter of the large silicon carbide balls is 10mm to 30mm, and the diameter of the small silicon carbide balls is 1mm to 5mm.
[0021] The mixed slurry is obtained by ball milling, and then dried and sieved to obtain a mixed powder. The preferred drying process is: the mixed slurry after ball milling is first evaporated and dried in a constant temperature box at 60-70°C for 12-24 hours to completely volatilize the ball milling medium. The preferred sieving process is: the mixed powder is sieved through an 80-200 mesh sieve.
[0022] The mixed powder is sintered by a hot pressing sintering system to obtain the high-strength SiC-based composite ceramic material. The sintering process is as follows: heating at a heating rate of 15 to 25°C / min; when the temperature rises to 600 to 700°C, adjusting the pressure to 10 to 20MPa and continuing to heat; when the temperature is 1000 to 1100°C, adjusting the heating rate to 8 to 12°C / min; when the temperature rises to 1500 to 1800°C, adjusting the pressure to 30 to 40MPa, and adjusting the heating rate to 5 to 7°C / min; when the temperature rises to 2000 to 2150°C, keeping the temperature and pressure for 30 to 60 minutes; then cooling with the furnace and releasing the pressure to obtain a WC / SiC composite ceramic block.
[0023] In the present invention, the density of the composite ceramic material obtained by the Archimedean drainage method is 99.02-99.26%; the density is 3.12-5.16 g / cm -3 ; The flexural strength of the composite ceramic material obtained by the three-point bending method test is 560.2-645.9MPa; The elastic modulus of the composite ceramic material obtained by pulse excitation method is 406.5-433.2 GPa; The fracture toughness of the composite ceramic material obtained by the slotting method is 4.31-7.49 MPa m 1 / 2 ; The average friction coefficient of the composite ceramic material obtained by the ball-disc friction method is 0.436-0.384; the specific wear rate is 15.23×10 -7 mm 3 ·N -1 ·m -1 ~6.67×10 -7 mm 3 ·N -1 ·m -1 .
[0024] The following examples are further cited to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only an example within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not limited to the specific values exemplified below. In the following embodiments, if there is no special explanation, the silicon carbide powder is α-SiC powder.
[0025] Example 1 87g of silicon carbide powder, 10g of tungsten carbide powder (10wt%), 1g of aluminum powder and 2g of carbon black were mixed and added to the SM-QB planetary ball mill, and the ball milling beads and anhydrous ethanol were added at a ball-to-material ratio of 2:1; the ball milling was performed at a speed of 300r / min for 4h, and the mixed slurry was obtained; the mixed slurry was poured into an enamel basin. It was placed in an electric constant temperature blast drying oven, dried at 60°C for 24h and passed through a 100 mesh sieve to obtain a mixed powder; Take 22g of the mixed powder and put it into a 40×40mm hot pressing mold. Heat it to 600℃ at 20℃ / min, then pass argon gas, continue to heat it to 1000℃, and pressurize it to 20MPa; then heat it to 1600℃ at 10℃ / min, pressurize it to 40MPa, then heat it to 1900℃ at 5℃ / min and keep the pressure, finally heat it to 2150℃ at 3℃ / min and keep the pressure for 1h, then cool it with the furnace and release the pressure, take out the sintered ceramic block, first use deionized water and then use ethanol to clean the ceramic surface, and obtain a SiC-based composite ceramic material. The composite ceramic block prepared in Example 1 was made into a sample for testing, and the test results are shown in Table 1.
[0026] Example 2 77g of silicon carbide powder, 20g of tungsten carbide powder (20wt%), 1g of aluminum powder and 2g of carbon black were mixed and added to the SM-QB planetary ball mill, and the ball milling beads and anhydrous ethanol were added at a ball-to-material ratio of 2:1; the ball milling was performed at a speed of 300r / min for 4h, and the mixed slurry was obtained; the mixed slurry was poured into an enamel basin. It was placed in an electric constant temperature blast drying oven, dried at 60℃ for 24h and passed through a 100 mesh sieve to obtain a mixed powder; Take 24g of the mixed powder and put it into a 40×40mm hot pressing mold. After heating to 600℃ at 20℃ / min, argon gas is passed through. After continuing to heat to 1000℃, pressurize to 20MPa; then heat to 1600℃ at 10℃ / min, pressurize to 40MPa, then heat to 1900℃ at 5℃ / min and maintain pressure, finally heat to 2150℃ at 3℃ / min and maintain pressure for 1h, then cool and release the pressure with the furnace, take out the sintered ceramic block, first use deionized water and then use ethanol to clean the ceramic surface, and obtain SiC-based composite ceramic material. The composite ceramic block obtained in Example 2 was made into a sample for testing, and the test results are shown in Table 1.
[0027] Example 3 67g of silicon carbide powder, 30g of tungsten carbide powder (30wt%), 1g of aluminum powder and 2g of carbon black were mixed and added to the SM-QB planetary ball mill, and the ball milling beads and anhydrous ethanol were added at a ball-to-material ratio of 2:1; the ball milling was performed at a speed of 300r / min for 4h, and the mixed slurry was obtained; the mixed slurry was poured into an enamel basin. It was placed in an electric constant temperature blast drying oven, dried at 60℃ for 24h and passed through a 100-mesh sieve to obtain a mixed powder; Take 26g of the mixed powder and put it into a 40×40mm hot pressing mold. After heating to 600℃ at 20℃ / min, argon is passed through. After continuing to heat to 1000℃, pressurize to 20MPa; then heat to 1600℃ at 10℃ / min, pressurize to 40MPa, then heat to 1900℃ at 5℃ / min and maintain pressure, finally heat to 2150℃ at 3℃ / min and maintain pressure for 1h, then cool and release the pressure with the furnace, take out the sintered ceramic block, first use deionized water and then use ethanol to clean the ceramic surface, and obtain SiC-based composite ceramic material. The composite ceramic block obtained in Example 3 was made into a sample for testing, and the test results are shown in Table 1.
[0028] Example 4 57g of silicon carbide powder, 40g of tungsten carbide powder (40wt%), 1g of aluminum powder and 2g of carbon black were mixed and added to the SM-QB planetary ball mill, and the ball milling beads and anhydrous ethanol were added at a ball-to-material ratio of 2:1; the ball milling was performed at a speed of 300r / min for 4h, and the mixed slurry was obtained; the mixed slurry was poured into an enamel basin. It was placed in an electric constant temperature blast drying oven, dried at 60℃ for 24h and passed through a 100 mesh sieve to obtain a mixed powder; Take 29g of the mixed powder and put it into a 40×40mm hot pressing mold. Heat it to 600℃ at 20℃ / min, then pass argon gas, continue to heat it to 1000℃, and pressurize it to 20MPa; then heat it to 1600℃ at 10℃ / min, pressurize it to 40MPa, then heat it to 1900℃ at 5℃ / min and keep the pressure, finally heat it to 2150℃ at 3℃ / min and keep the pressure for 1h, then cool it with the furnace and release the pressure, take out the sintered ceramic block, first use deionized water and then use ethanol to clean the ceramic surface, and obtain a SiC-based composite ceramic material. The composite ceramic block obtained in Example 4 was made into a sample for testing, and the test results are shown in Table 1.
[0029] Example 5 47g of silicon carbide powder, 50g of tungsten carbide powder (50wt%), 1g of aluminum powder and 2g of carbon black were mixed and added to the SM-QB planetary ball mill, and the ball milling beads and anhydrous ethanol were added at a ball-to-material ratio of 2:1; the ball milling was performed at a speed of 300r / min for 4h, and the mixed slurry was obtained; the mixed slurry was poured into an enamel basin. It was placed in an electric constant temperature blast drying oven, dried at 60℃ for 24h and passed through a 100 mesh sieve to obtain a mixed powder; 33g of mixed powder was put into a 40×40mm hot pressing mold, and the temperature was raised to 600℃ at 20℃ / min, and then argon was introduced. After the temperature was further raised to 1000℃, the pressure was increased to 20MPa; then the temperature was raised to 1600℃ at 10℃ / min, and the pressure was increased to 40MPa, and then the temperature was raised to 1900℃ at 5℃ / min and the pressure was maintained, and finally the temperature was raised to 2150℃ at 3℃ / min and the pressure was maintained for 1h, and then the furnace was cooled and the pressure was released, and the sintered ceramic block was taken out, and the ceramic surface was first cleaned with deionized water and then with ethanol to obtain a SiC-based composite ceramic material. The composite ceramic block obtained in Example 5 was made into a sample for testing, and the test results were shown in Table 1.
[0030] Comparative Example 1 The preparation process of the high-strength SiC-based composite ceramic material in this comparative example 1 is the same as that in Example 1, except that: 87.4g of silicon carbide powder, 10g of tungsten carbide powder (10wt%), 0.6g of B4C powder and 2g of carbon black are mixed and added to the SM-QB planetary ball mill, and ball milling beads and anhydrous ethanol are added at a ball-to-material ratio of 2:1; ball milling is performed at a speed of 300r / min for 4h, and mixed evenly to obtain a mixed slurry; the mixed slurry is poured into an enamel basin. Put it into an electric constant temperature blast drying oven, dry it at 60°C for 24h and pass it through a 100-mesh sieve to obtain a mixed powder; Take 22g of the mixed powder and put it into a 40×40mm hot pressing mold. Heat it to 600℃ at 20℃ / min, then pass argon gas, continue to heat it to 1000℃, and pressurize it to 20MPa; then heat it to 1600℃ at 10℃ / min, pressurize it to 40MPa, then heat it to 1900℃ at 5℃ / min and maintain the pressure, finally heat it to 2150℃ at 3℃ / min and maintain the pressure for 1h, then cool it with the furnace and release the pressure, take out the sintered ceramic block, first use deionized water and then use ethanol to clean the ceramic surface to obtain SiC-based composite ceramic material. The composite ceramic block prepared in this comparative example 1 was made into a sample for testing, and the test results are shown in Table 1. In comparative example 1, the B element in B4C will react with WC to form W2B5. The performance of W2B5 is lower than that of WC, which will reduce the performance of the sample.
[0031] Comparative Example 2 The preparation process of the high-strength SiC-based composite ceramic material in this comparative example 2 is similar to that in Example 1, except that: 97g of silicon carbide powder, 0g of tungsten carbide powder (0wt%), 1g of Al powder and 2g of carbon black are mixed and added to an SM-QB planetary ball mill, and ball milling beads and anhydrous ethanol are added at a ball-to-material ratio of 2:1; ball milling is performed at a speed of 300r / min for 4h, and mixed evenly to obtain a mixed slurry; the mixed slurry is poured into an enamel basin. Put it into an electric constant temperature blast drying oven, dry it at 60°C for 24h and pass it through a 100-mesh sieve to obtain a mixed powder; Take 22g of the mixed powder and put it into a 40×40mm hot pressing mold, raise the temperature to 600℃ at 20℃ / min, then pass argon, continue to raise the temperature to 1000℃, and pressurize it to 20MPa; then raise the temperature to 1600℃ at 10℃ / min, pressurize it to 40MPa, then raise the temperature to 1900℃ at 5℃ / min and maintain the pressure, finally raise the temperature to 2150℃ at 3℃ / min and maintain the pressure for 1h, then cool and release the pressure with the furnace, take out the sintered ceramic block, first use deionized water and then use ethanol to clean the ceramic surface, and obtain a SiC-based composite ceramic material. The composite ceramic block prepared in this comparative example 1 was made into a sample for testing, and the test results are shown in Table 1.
[0032] Table 1 shows the properties of the SiC-based composite ceramic material prepared by the present invention:
Claims
1. A method for preparing a high-strength SiC-based composite ceramic material, characterized in that: include: (1) mixing SiC powder, WC powder, an aluminum source and a carbon source to obtain a mixed powder; (2) Hot pressing and sintering the mixed powder to obtain the high-strength SiC-based composite ceramic material.
2. The preparation method according to claim 1, characterized in that: The SiC powder is α-SiC powder with a particle size of ≤1 μm; the WC powder has a particle size of ≤2 μm.
3. The preparation method according to claim 1, characterized in that: The total weight of SiC powder, WC powder, aluminum source and carbon source is recorded as 100wt%, wherein SiC powder accounts for 44% to 88%, and WC powder accounts for 10% to 50%.
4. The preparation method according to claim 1, characterized in that: The aluminum source is at least one of aluminum powder and aluminum oxide powder; the added amount of the aluminum source is 1 to 3 wt % of the total mass of the mixed powder.
5. The preparation method according to claim 1, characterized in that: The carbon source is at least one of carbon black, activated carbon, graphite, glucose, starch and phenolic aldehyde; and the amount of the aluminum source added is 1-3wt% of the total mass of the mixed powder.
6. The preparation method according to claim 1, characterized in that: The mixing method is ball milling; The parameters of the ball milling mixing using the SM-QB planetary ball mill include: the ball milling medium is anhydrous ethanol, the ratio of the ball milling medium to the mixed powder is (0.5-1):1; the ball-to-material ratio is (3-1):1, preferably 2:1; the ball milling speed is 200-400 r / min, and the ball milling time is 4-12 h.
7. The preparation method according to claim 6, characterized in that: The grinding balls used for ball milling and mixing are composed of large silicon carbide balls and small silicon carbide balls in a mass ratio of (0.1-10):1; wherein the diameter of the large silicon carbide balls is 10mm-30mm, and the diameter of the small silicon carbide balls is 1mm-5mm.
8. The preparation method according to claim 6, characterized in that: After the ball milling is completed, the mixture is dried and sieved; the drying temperature is 60-70° C. and the time is 24-36 hours; and the sieving is through a sieve of 80-200 meshes.
9. The preparation method according to claim 1, characterized in that: The parameters of the hot pressing sintering include: a pressure of 30-40 MPa, a temperature of 2000-2150° C., and a time of 30-60 minutes.
10. The preparation method according to claim 9, characterized in that: The parameters of the hot pressing sintering include: First, the temperature is raised to 600-700°C at a heating rate of 15-25°C / min, and the pressure is adjusted to 10-20MPa; Then, the temperature is raised to 1000°C to 1100°C at a heating rate of 15 to 25°C / min; Adjust the heating rate to 8-12°C / min and continue to heat to 1500-1800°C, and adjust the pressure to 30-40MPa; The second heating rate is adjusted to 5-7°C / min and the temperature is continued to rise to 2000-2150°C and the temperature is kept at a constant temperature and pressure for 30-60 minutes; Finally, the furnace is cooled to room temperature and the pressure is released.
Citation Information
Patent Citations
Method for preparing silicon carbide-aluminum nitride (SiC-AlN) solid solution ceramic powder
CN102515767A
Preparation method for compact silicon carbide ceramics free of boron or rare earth elements
CN104926309A
Preparation method of SiC composite ceramic material
CN115819090A
Manufacturing method of zirconium diboride-silicon carbide composite
KR1020110077154A
Sintered silicon carbide
US3836673A
Cited By
Preparation method of high-toughness beta-SiC nano ceramic
CN120025175A